الخصائص الإسلامية في شخصية المرأة الملايوية في الحكايات الملايوية القديمة: دراسة أدبية تحليلية: Islamic Values in the Characteristics of Malay Woman in Classical Malay Texts: A Literary Analysis - Abd Rahim, Nadiah; Ahmad H. Osman, Rahmah; Abd Manap, Nur Fazlina (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص يتميز كل عرق في العالم بثقافة معينة، وهي التي تشكل شخصية الانسان، والعرق الملايو له ثقافتة وعاداته الخاصة، ولا سيما المرأة الملايوية، وفي هذا العصر وبسبب عدم التمسك بالدين والالتزام بعادات الملايو تحدث مشاكل اجتماعية كثيرة بين النساء. يرى هذا البحث أن الحكايات الملايوية القديمة تكون مهملة أو منسية ونصوصا غير معروفة للأجيال الحالية. لذلك، يهدف البحث إلى الكشف عن الخصائص الإسلامية الموجودة في شخصية المرأة الملايوية في الحكايات الملايوية القديمة المختارة مثلا من الشعر كشعر سيتي زبيدة، حكاية هغ تواه، وتحفة النفيس، و حكاية ملوك باساي، وسلالة السلاطين مع بيان خصائصها وشرح بعض الأمثلة منها. يعتمد هذا البحث على المنهج التحليلي في الأدب من خلال مراجعة بعض المراجع والكتب المرتبطة في اللغة الملايوية، ثم ترجمت الباحثة المعلومات الواردة في البحث إلى اللغة العربية، وفي هذه الدراسة تحليل بعض خصائص الإسلام من خلال النظر إلى شخصية المرأة الملايوية خاصة للزوجة والأم والعاملة في خمس من الحكايات الملايوية القديمة. وقد وجد هذا البحث سبعة من الخصائص الإسلامية في شخصيات المرأة الملايوية من الحكايات المختارة منها الصبر والقوة، وخاصية تَدَيُّنِ المرأة، وخاصية وفاء المرأة لزوجها، وخاصية نقاء المرأة، وخاصية حب وعطف الأم، وخاصية المرأة المستقلة، وخاصية قيادة المرأة. Abstract Every race in the world is characterized by a special culture that generates an individual’s personality. Malay emphasizes the culture and customs of all society, especially women, but there are many social problems among women in this era because of the lack of adherence to religion and adherence to Malay customs. According to this research, ancient Malay tales are neglected or forgotten and its texts are unknown to present generations. Therefore, the research aims to discover the Islamic characteristics found in Malay women’s characters in selected ancient Malay tales such as from the Poem of Siti Zubaydah, the tale of Hang Tuah, the masterpiece of the Melaka, the tale of the kings of Pasai and the dynasty of the sultans with their characteristics and examples. This research is based on the analytical approach in literature by reviewing some related references and books in the Malay language. This research has found seven Islamic characteristics in the characters of Malay women from the selected tales, such as patience and strength, the religious characteristic of women, the characteristic of a woman’s loyalty to her husband, the characteristic of a woman’s purity, the characteristic of mother’s love and sympathy, the characteristic of independent women, and the characteristic of women’s leadership.